Strategi Pengembangan Profesionalisme Guru Madrasah Ibtidaiyah - Firdaus, Muhammad (ELEMENTARY : Journal of Primary Education, 2024)
. The Madrasah Ibtidaiyah Teacher Professionalism Development Strategy is a systematic effort to improve the quality and competence of teachers at the Islamic primary school level. This research examines the various approaches and methods used to strengthen teachers' pedagogical abilities, content knowledge and managerial skills. The approaches analyzed include continuous training, curriculum development, mentoring and the use of educational technology. The results show that effective strategies involve teachers' active participation in professional development programs, support from educational institutions and supportive policies from the government. Teacher professional development not only improves teaching quality and student learning outcomes but also contributes to improving the overall quality of education in madrasah ibtidaiyah.